The central scaffold protein CEP350 coordinates centriole length, stability, and maturation - Karasu, Onur Rojhat; Neuner, Annett; Atorino, Enrico; Pereira, Gislene; Schiebel, Elmar (The journal of cell biology, 2022)
The centriole is the microtubule-based backbone that ensures integrity, function, and cell cycle-dependent duplication of centrosomes. Mostly unclear mechanisms control structural integrity of centrioles. Here, we show that the centrosome protein CEP350 functions as scaffold that coordinates distal-end properties of centrioles such as length, stability, and formation of distal and subdistal appendages. CEP350 fulfills these diverse functions by ensuring centriolar localization of WDR90, recruiting the proteins CEP78 and OFD1 to the distal end of centrioles and promoting the assembly of subdistal appendages that have a role in removing the daughter-specific protein Centrobin. The CEP350-FOP complex in association with CEP78 or OFD1 controls centriole microtubule length. Centrobin safeguards centriole distal end stability, especially in the compromised CEP350−/− cells, while the CEP350-FOP-WDR90 axis secures centriole integrity. This study identifies CEP350 as a guardian of the distal-end region of centrioles without having an impact on the proximal PCM part.